Análise numérica do comportamento de pavimentos constituídos de lajes lisas de concreto protendido - La Torre Cubas, Vanessa (2015)
Concrete flat slabs prestressed with unbounded greased strands have been used in building floors over the last years. This structural solution is ideal when the columns are regularly distributed. In addition, it is known that prestressed floors have some technical advantages when compared to the traditional solution in reinforced concrete, mainly in cases of large spans and when lighter elements are required. The objective of the present work is to propose practical criteria for the design of flat slab prestressed concrete floors, for the cases of uniform thickness slabs and waffle slabs, aiming at complying with serviceability limit state. A parametric study was carried out to analyze the stress distribution in prestressing load introduction zones and the influence of the columns in retaining prestressing loads. The investigation was conducted using finite element models in which shell and frame elements were used to represent the slabs and the columns. For the case of waffle slabs, flanges and webs were modeled with shell and frame elements, respectively, taking into consideration the eccentricity between these two elements.